Tingkatkan Kesantunan Berbahasa Melalui Penerapan 4 Kata Ajaib - Melicha Athalia Pelawi; Bengkel Ginting (Universitas Maritim AMNI Semarang, 2024)
Field Work Practice II is one of the mandatory courses for social welfare students in implementing the knowledge they have learned on a mezzo or macro scale. The author carried out this practicum II activity at the Yayasan Fondasi Hidup Indonesia which is located on Jalan Kenanga Raya No. 50, Medan Selayang. The author will carry out a mini project in one of the assisted communities of the Yayasan Fondasi Hidup Indonesia in Siguci Village regarding language politeness by applying 4 magic words and a total of 30 clients from grades 1-3 of elementary school. The author carried out a mini project at the mezzo intervention level using the intervention stages method group work in general. This mini project shows that polite language can shape good character through the application of the 4 magic words.